Analisis Faktor Yang Memengaruhi Ekspor Furnitur Kayu Indonesia Ke Amerika Serikat - Febrianti, Feby; Kartika Yudha, I Made Endra (Innovative: Journal Of Social Science Research, 2024)
Import-export activities are a form of international trade that can influence economic growth. This research was conducted to determine the influence of IHPB, Exchange Rates, SVLK Policy and the 2012 Raw Wood Export Prohibition Policy on Indonesian wooden furniture exports to the United States in 2006-2022. This research was conducted quantitatively with time series data. Methodology that used in this research is ARDL. This research provides results which state that 1) The wholesale price index, exchange rate, and the policy of banning raw wood exports in the long term influence the value of Indonesian wooden furniture exports to the United States in 2006-2022, while the SVLK policy has no effect on Indonesian wooden furniture exports to the United States 2006-2022. 2) The wholesale price index, exchange rate, SVLK policy and the policy of banning raw wood exports in the short term have an influence on Indonesian wooden furniture exports to the United States in 2006-2022.